Les Facteurs De Developpement Des Actıvıtes Commercıales Sur Les Marches D’abıdjan - Ferdinand, Ake Ohouo (European Scientific Journal, ESJ, 2016)
The metropolis of Abidjan, economic capital of the Ivory Coast is a big west African metropolis. She is composed of ten townships that shelter each several markets. These markets play a primordial role in the development of the commercial activities. Indeed, every township shelters commercial infrastructures localized in the different districts. These markets are of variable size because one finds some of big and of small size. They knew an evolution since the years 1976 until our days. These markets are constructed either by the public powers, either by the promoters deprived according to the Build Operate and Transfer system. The system is a contract of constructional concession of public work a deprived entrepreneur’s that exploits it during a certain time until the amortization of the working assets. These markets specialized in various domains of activities; offer the abidjanaise population, those of the inside of the country and even of the under-region panoply of articles that makes of this city biggest shopping mall of the country. The periods of exercise of these markets vary. The majority of the markets of Abidjan exercises in the day. On the other hand, some lead their activities in the evening, until late the night and are called of the night markets. The flourishing economic activities of the markets of Abidjan are bound to several factors of which the human factors and the economic factors more especially the economic activities that provide to the different worked the products necessary to the satisfaction of the needs of the consumers. These products provided by the economic activities are at the origin of the development of the commercial activities on the markets in the city of Abidjan.